Using autoregressive integrated moving average (ARIMA) models to predict the number of patient admission in Paediatric clinic at a private hospital in Kuantan - Mohamed, Bahari; Mohamad, Meriati (Wardah Communication Sdn. Bhd, 2018)
This study present autoregressive integrated moving average (ARIMA) models to forecast monthly patient demand for Paediatric clinic at a private hospital in Kuantan. The ARIMA model developed hold potential for providing operational decision support in the hospital. The forecasting success attained for the Paediatric clinic could aid managers to make capacity and advance planning in the wards and hospital. The ARIMA model was developed from time series data routinely-collected at Paediatric clinic. The study evaluated patient demand at Paediatric clinic by using time series data collected from year 2012 until year 2017. Analyses of time series data of Paediatric clinic produce ARIMA (2, 0, 2) model of monthly data. The ARIMA (2, 0, 2) give rise to MAPE of 11.988 percent respectively, therefore ARIMA (2, 0, 2) model was selected for modelling and forecasting paediatric patient demand based on the lowest MAPE values. The out of sample forecast by using ARIMA (2, 0, 2) model indicated a fluctuation of monthly paediatric patients demand, being the lowest was 325 and the highest was 400 patients that could receive treatment from the clinic in a month. The forecasting models then could be extended to other clinics.